HIV and antiretroviral drug resistance - N. V. Nemchinova; T. A. Bairova; A. Yu. Sambyalova; E. V. Belyaeva; O. A. Ershova (Журнал инфектологии)
The article presents modern views on the causes of the formation of drug-resistant HIV strains. The main reasons for the ineffectiveness of antiretroviral therapy are low patient adherence to treatment, lack of combination therapy, and high rate of viral recombination, which leads to the emergence of HIV drug resistance mutations. The data on HIV drug resistance mutations and their prevalence in different populations and in different age groups were analyzed. The most common HIV drug resistance mutations M184V and K103N are found in both acquired and transmitted HIV drug resistance, these mutations cause drug resistance to nucleoside and non-nucleoside reverse transcriptase inhibitors and are found in people living with HIV. Due to the high prevalence of drug-resistant strains, testing of people with HIV infection for HIV drug resistance mutations is necessary in cases of treatment failure and in patients in areas where the percentage of transmitted drug resistance is high.